Mycosis Fungoides: A Case Report - Joshi, Anisha; Pathak Thapa, Deeptara (Nepal Journal of Dermatology, Venereology & Leprology, 2021)
Mycosis fungoides is the most common primary cutaneous T-cell lymphoma and is recognized as one of the rare malignant skin neoplasms. Hypopigmented mycosis fungoides is a variant of mycosis fungoides, described in dark-skinned individual and Asian patients. We report a case of 32 years old Nepalese female who had presented with multiple asymptomatic hypopigmented macules over the bilateral arms, thighs, abdomen, back of trunk and buttocks. Skin biopsy revealed few atypical cells (small/medium-sized, cerebriform nuclei with halo) confined to epidermis with epidermotropism. Immunohistochemistry showed CD3, CD4, CD5 and CD8 positivity. The patient was managed with topical steroids, oral methotrexate and phototherapy, and she is on regular follow up. As the disease has an indolent clinical course, long term follow up is necessary.